In vitro Analysis of Neurospheres Derived from Glioblastoma Primary Culture: A Novel Methodology Paradigm - Pavon, Lorena F.; Marti, Luciana C.; Sibov, Tatiana T.; Malheiros, Suzana M.; Brandt, Reynaldo A.; Cavalheiro, Sergio; Gamarra, Lionel (Frontiers in Neurology, 2014)
Glioblastomas are the most lethal primary brain tumour frequently relapse or progress as focal masses after radiation, suggesting that only a fraction of tumour cells are responsible for the tumor regrowth. The identification of a brain tumour cell subpopulation with potent tumorigenic activity supports the cancer stem cell hypothesis in solid tumours. The goal of this study was to determine a methodology for the establishment of primary human glioblastoma stem cell lines. Our aim was achieved by taking the following approaches: i) the establishment of primary glioblastoma cell culture; ii) isolation of neurospheres derived from glioblastoma primary culture and derived straight from the tumor; iii) CD133 microbeads purified neurospheres by MACS, iv) Formation of subspheres in the CD133+ population, v) Study of the expression level of GFAP, CD133, Nestin, Nanog, CD34 and Sox2 markers on tumor subspheres. Here, we describe a successful method for isolation of CD133+ cell population and establishment of glioblastoma neurospheres from this primary culture, which are more robust than the ones derived straight from the tumor. Highlight that the neurospheres derived from glioblatoma primary culture showed 89% expression of CD133+ cells, whereas tumor-derived neurospheres showed a 60% expression of CD133+ cells. These results show a higher concentration of CD133+ cells in neurospheres derived from glioblastoma primary culture. These CD133+ fractions were able to further generate subspheres. The subspheres derived from glioblastoma primary culture presented a well defined morphology while the ones derived form the fresh tumor were sparce and less robust. The negative fraction of CD133 cells was unable to generate subspheres. The tumor subspheres expressed GFAP, CD133, Nestin and Nanog. The present study describes an optimization of isolation of neurospheres/subspheres derived from glioblastoma primary culture by process of selection of CD133+ adherent stem cell.